Intersexual Differences in the Gene Expression of Phoneutria depilata (Araneae, Ctenidae) Toxins Revealed by Venom Gland Transcriptome Analyses (2023)
The wandering spider, Phoneutria depilata, is one of Colombia’s most active nocturnal arthropod predators of vertebrates and invertebrates. Its venom has been a relevant subject of study in the last two decades. However, the scarcity of transcriptomic data for the species limits our knowledge of the distinct components present in its venom for linking the mainly neurotoxic effects of the spider venom to a particular molecular target. The transcriptome of the P. depilata venom gland was analyzed to understand the effect of different diets or sex and the impact of these variables on the composition of the venom. We sequenced venom glands obtained from ten males and ten females from three diet treatments: (i) invertebrate: Tenebrio molitor, (ii) vertebrate: Hemidactylus frenatus, and (iii) mixed (T. molitor + H. frenatus). Of 17,354 assembled transcripts from all samples, 65 transcripts relating to venom production differed between males and females. Among them, 36 were classified as neurotoxins, 14 as serine endopeptidases, 11 as other proteins related to venom production, three as metalloprotease toxins, and one as a venom potentiator. There were no differences in transcripts across the analyzed diets, but when considering the effect of diets on differences between the sexes, 59 transcripts were differentially expressed. Our findings provide essential information on toxins differentially expressed that can be related to sex and the plasticity of the diet of P. depilata and thus can be used as a reference for venomics of other wandering spider species.